2012
DOI: 10.1371/journal.ppat.1002556
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Monomeric Intermediates during VSV Glycoprotein Structural Transition

Abstract: Entry of enveloped viruses requires fusion of viral and cellular membranes, driven by conformational changes of viral glycoproteins. Crystal structures provide static pictures of pre- and post-fusion conformations of these proteins but the transition pathway remains elusive. Here, using several biophysical techniques, including analytical ultracentrifugation, circular dichroïsm, electron microscopy and small angle X-ray scattering, we have characterized the low-pH-induced fusogenic structural transition of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 35 publications
4
67
0
Order By: Relevance
“…On the surface of a virion at neutral pH and above, our results together with published data indicate that full-length G is in equilibrium between the prefusion trimer conformation and flexibly extended monomers (10,(20)(21)(22). In the absence of a target membrane, irreversible transition of virion G to its conformation at the end of a complete fusion reaction would require that three subunits come together, fold back, and insert their fusion loops into the viral membrane (Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…On the surface of a virion at neutral pH and above, our results together with published data indicate that full-length G is in equilibrium between the prefusion trimer conformation and flexibly extended monomers (10,(20)(21)(22). In the absence of a target membrane, irreversible transition of virion G to its conformation at the end of a complete fusion reaction would require that three subunits come together, fold back, and insert their fusion loops into the viral membrane (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…G th was cleaved and purified from virus particles as described in ref. 21 with the following modifications. In the cleavage reaction, the concentration of WT virus was 10 mg/mL, of G-W72A virus 11.1 mg/mL, and of thermolysin 0.6 mg/mL.…”
mentioning
confidence: 99%
“…In the case of WT G, the prefusion trimer, although detected at the viral surface (16), is not stable in solution and only monomers are detected at high pH (14,17). On the other hand, at low pH, the postfusion trimer is stable.…”
Section: Resultsmentioning
confidence: 99%
“…For both RABV and VSV, it has been demonstrated that low-pH-induced structural transition of G is reversible (14,15). In fact, at the viral surface, there is a pH-dependent thermodynamic equilibrium between different states of G, which is shifted toward the trimeric postfusion form at low pH (16)(17)(18). This is the main difference between rhabdoviral G and other viral fusion glycoproteins activated at low pH for which the prefusion conformation is metastable and, as a consequence, the low-pH-induced structural transition is irreversible (4).…”
mentioning
confidence: 99%
“…Both have a single glycoprotein that forms trimeric structures in the viral envelope. 5 A key difference between these viruses is the ability of rabies to undergo retrograde transport. Rabies virus infects nerves in the peripheral nervous system, and subsequently the central nervous system by trans-synaptic spread.…”
Section: Introductionmentioning
confidence: 99%